A Psychoanalysis of Trauma in the Animated Movie “Encanto” - Habiba Farisa Asfahani; Teguh Sulistyo; Purnawati Maria (UIBU, 2025)
Trauma is a psychological disorder that can impact the dynamics of connections between generations and is emotionally inherited in generations. Individual and intergenerational trauma is the primary themes that drive conflict within the Madrigal family in the animated film “Encanto”. This study examines the recovery processes portrayed in the movie and determines the psychological effects of trauma on individuals and their families using Caruth's trauma theory and Hirsch's intergenerational trauma theory. The method used is descriptive in which the researchers collect data through film observation, theoretical studies, and analysis of scenes and dialog that depict trauma and the recovery process. The findings demonstrated how Abuela's character's trauma from her husband's death led to psychological distress and heightened standards within the Madrigal family, which in turn affected other family members. This dynamic serves as an example of the trauma cycle that does not only causes people to become isolated but also prevents their ability to develop personally within the family context. The movie portrays a process of recovery that enables family members to go from feeling alienated to feeling united through admissions and shared memories.